2020
DOI: 10.3390/medicina56070353
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Procedural Thromboembolisms after Mechanical Thrombectomy for Acute Ischemic Stroke

Abstract: Background and objective: Procedural thromboembolisms after mechanical thrombectomy (MT) for acute ischemic stroke has rarely been studied. We retrospectively evaluated factors associated with procedural thromboembolisms after MT using diffusion-weight imaging (DWI) within 2 days of MT. Materials and Methods: From January 2018 to March 2020, 78 patients with acute ischemic stroke who underwent MT were evaluated using DWI. Procedural thromboembolisms were defined as new cerebral infarctions in other territories… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…This current study further confirmed the important role of age in the unsatisfactory outcomes and in-hospital mortality. In practice, the age of patients in our study was relatively young compared with some other studies (23,24). Sojka et al reported that the mortality after 90 days was as high as 47.4 % in acute ischemic stroke patients aged more than 90 years old (25).…”
Section: Discussionmentioning
confidence: 56%
“…This current study further confirmed the important role of age in the unsatisfactory outcomes and in-hospital mortality. In practice, the age of patients in our study was relatively young compared with some other studies (23,24). Sojka et al reported that the mortality after 90 days was as high as 47.4 % in acute ischemic stroke patients aged more than 90 years old (25).…”
Section: Discussionmentioning
confidence: 56%
“…Complications after an MT for an AIS include a procedural hemorrhagic complication and procedural thromboembolism. When previous studies focused on the efficacy and safety of an MT for an AIS, recanalization was considered a primary outcome, and a procedural hemorrhagic complication was considered a safety outcome [ 1 , 15 ]. However, procedural thromboembolism has not been considered necessary during the MT for an AIS, because the purpose of an MT for an AIS is to achieve the recanalization of the occluded vessels.…”
Section: Discussionmentioning
confidence: 99%
“…A mechanical thrombectomy (MT) is a standard treatment for an acute ischemic stroke caused by large artery occlusion, due to its site specificity and high recanalization rates [1][2][3]. The endovascular approach has the advantage of faster and safer access to the cerebral arteries; however, it also has a risk of procedural thromboembolism [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations